Exploring Students Perception of Manikin Based Training in a Medical Skills Lab (Medical Forum Monthly, 2023)
Objective: To assess the perception of students at the University College of Medicine & Dentistry regarding their training on manikins in a skills lab.Study Design: Cross Sectional studyPlace and Duration of Study: This study was conducted at the University College of Medicine and Dentistry, The University of Lahore from January 2023 to June 2023.Materials and Methods: Data was collected from final year MBBS students using a pre validated 23 items questionnaire. A total of 121 students were included in the study. SPSS version 23 was used for data analysis. Mean ± SD and frequency (percentages) were calculated. Chi Square test was applied and p values less than or equal to 0.05 was taken as significance.Results: A total of 121 participants were enrolled, comprising 78 female students (57%) and 59 male students (43%). The calculated mean of the sum of all 23 questionnaire items was 73.16 ± 10.33, with individual item means at 2.96 ± 0.449. These results suggest a noteworthy inclination of students towards skill laboratory training, indicating a favorable perception of this educational approach. Statistical analysis revealed a significantly high frequency of students expressing positive attitudes towards skill laboratory training (p < 0.05).Conclusion: Training on mannequins in a skills lab is a preferred teaching methodology for students, and it greatly aids them in achieving their desired learning outcomes.